The competitive scenario of building technology & ideas ltd. (bti) and the path to reach the number one position in real estate sector - Nine, Md. Julker (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.